2007
DOI: 10.1007/s11060-007-9508-y
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy predicts proliferative activity in diffuse low-grade gliomas

Abstract: The aim of the study was to investigate the ability of (1)HMRS to reflect proliferative activity of diffuse low-grade gliomas (WHO grade II). Between November 2002 and March 2007, a prospective study was performed on consecutive patients with suspected supratentorial hemispheric diffuse low-grade tumors. All the patients underwent MR examination using uniform procedures, and then surgical resection or biopsy within 2 weeks of the MR examination. Proliferative activity of the tumors was assessed by Ki-67 immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 41 publications
1
30
0
4
Order By: Relevance
“…In previous study it was reported that the 45% increase of tCho indicates tumor progression, while an increase of up to 35% indicates its stable status (Pinker et al 2012). The direct correlation was also declared between the tCho/tNAA, tCho/tCr and the proliferation marker Ki-67 (Guillevin et al 2008;Toyooka et al 2008) which is a predictor of aggressive clinical tumor manifestation (Horska and Barker 2010;Kao et al 2013). In this study, in addition to elevated values of tCho/tCr and tCho/tNAA decreased levels of tNAA/tCr were also observed in glioblastoma-affected brain tissue compared to the healthy areas.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In previous study it was reported that the 45% increase of tCho indicates tumor progression, while an increase of up to 35% indicates its stable status (Pinker et al 2012). The direct correlation was also declared between the tCho/tNAA, tCho/tCr and the proliferation marker Ki-67 (Guillevin et al 2008;Toyooka et al 2008) which is a predictor of aggressive clinical tumor manifestation (Horska and Barker 2010;Kao et al 2013). In this study, in addition to elevated values of tCho/tCr and tCho/tNAA decreased levels of tNAA/tCr were also observed in glioblastoma-affected brain tissue compared to the healthy areas.…”
Section: Resultssupporting
confidence: 66%
“…However, it is possible to spectroscopically measure precursors of their synthesis and products of their degradation as the tCho signal contributors (Solivera and Law 2009;Ha et al 2013). Since the level of tCho particularly reflects the concentration of phosphocholine which is more than twice increased in highgrade gliomas (Lupo et al 2007;McKnight and Wladman 2010), tCho is suitable for monitoring tumor carcinogenesis (Guillevin et al 2008;Housni and Boujraf 2013). In previous study it was reported that the 45% increase of tCho indicates tumor progression, while an increase of up to 35% indicates its stable status (Pinker et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 According to the previous literature, this index is correlated with various advanced MR imaging parameters. 8,20,21 In this study, we performed a comparative review of multiple parameters obtained with pulse sequences evaluated by using 3T MR imaging and glioma grading in newly diagnosed patients with glioma. Our purpose was to evaluate whether the parameters provide useful, complementary information and whether this combination of parameters shows the best performance for grading cerebral gliomas.…”
mentioning
confidence: 99%
“…rCBV has also been correlated with glucose uptake and tumor angiogenesis in human gliomas (22,23). In a previous study we demonstrated a correlation between different Ki-67 values and specific spectral profiles, eg, the resonance of lactate was an independent predictive factor of Ki-67 values that are greater than 4% (16). Moreover, we have previously shown a correlation between the resonance of free lipids and the presence of cellular atypia.…”
Section: Discussionmentioning
confidence: 73%